Design of a family of multi-DOF drive systems for fewer limb parallel mechanisms. (June 2020) - Li, Luquan; Fang, Yuefa; Wang, Lin
Abstract: Inspired by fewer-limb multi-degree-of-freedom (DOF) parallel mechanisms (PMs), a systematic method that synthesizes multi-DOF drive systems is presented based on Lie group theory. Multi-DOF drive systems can generate more DOFs motion than a pure rotation or a pure translation. The benefit of such multi-DOF drive systems is that all motors are mounted on a fixed base. The topological structures of novel single-loop PMs and multi-DOF drive systems are proposed. A class of 2-DOF drivers are designed. The motion types of the multi-DOF drive systems are systematically synthesized based on Lie group theory. Moreover, a family of 3-DOF drive systems are developed based on the designed 2-DOF drivers and synthesized motion types. Multi-DOF drive systems play a key role in simplifying the structure of PMs to improve the motion characteristics of PMs. A novel single-loop PM is designed to illustrate the application of the designed multi-DOF drive system, and kinematics analysis is performed to reveal the motion characteristics of the single-loop PM with the novel multi-DOF drive system.